(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
This article proves theorems on cardinal properties of weakly separable spaces, which are one of the important spaces of topology. In particular, the images of weakly separable spaces in different mapping are presented with proofs of theorems about weakly separable spaces, and good results were obtained